2021
DOI: 10.1186/s40814-021-00911-2
|View full text |Cite
|
Sign up to set email alerts
|

Using the Behaviour Change Wheel to design an intervention for partner abusive men in drug and alcohol treatment

Abstract: Background We aimed to establish what core elements were required in a group therapy programme for men who disclose perpetrating intimate partner abuse in a substance use setting and develop, and test the feasibility of delivering an intervention in this setting. Methods We describe the theoretical development and feasibility testing of an integrated substance use and intimate partner abuse intervention (‘ADVANCE’) for delivery in substance use ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…80 studies from 111 reports were included in this review (see figure 1). Data extracted from the included studies are summarised in online supplemental appendix 4 and figure 2 51 68–177…”
Section: Resultsmentioning
confidence: 99%
“…80 studies from 111 reports were included in this review (see figure 1). Data extracted from the included studies are summarised in online supplemental appendix 4 and figure 2 51 68–177…”
Section: Resultsmentioning
confidence: 99%
“…For example, a systematic review conducted by Gilchrist et al (2015) of the effectiveness of cognitive behavioural therapy with anger management components for IPV perpetrators who used alcohol showed promising results in the short term and suggested that more research is needed to match this group of IPV perpetrators with specific intervention programs that address their individual needs. Enhancing distress tolerance for perpetrators who use substances has been shown to promote positive behaviour change and skills development ( Gilchrist, Johnson, et al, 2021 ; Gilchrist, Potts, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Developed to identify the intervention components most appropriate to effect the desired change, the BCW has previously been used for intervention development and evaluation and to structure reviews – including in interventions focusing on alcohol [ 57 , 58 ]. For example, Gilchrist et al used the BCW during the theoretical development and feasibility testing of an intervention addressing substance use and intimate partner violence [ 59 ]. Of note, pre-specifying the behaviour change mechanisms in the design phase allowed us to, not only develop the intervention, but also to adapt it to the changing environment following COVID-19 and the financial crisis.…”
Section: Discussionmentioning
confidence: 99%